(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, some of the unusual combinations used by writers in artistic texts are identified, and the main role of these combinations in expressing the content of the work and the characteristics of linguopoetic actualization are analyzed. It has been shown that the use of such unusual combinations not only reveals the creativity of the writer, but also increases the artistic-aesthetic content and colorfulness of the work, increases the reader’s interest in reading the work, and encourages deep observation.